A rare case of combined ileal lipoma and heterotopic gastric mucosa as the leading pathological point for adult ileo-ileal intussusception - Pande, Kricha; Rana, Reena; Aryal, Gopi; Acharya, Shoshan (Nepal Mediciti Medical Journal, 2024)
Intussusception is defined as telescoping of one segment of bowel into another one. It is an uncommon cause of intestinal obstruction in adults with a reported incidence of 1 in 1300 abdominal cases presenting as obstruction. Intussusception as a cause of intestinal obstruction in adults is rare. There is invariably an underlying pathology which leads to intussusception in adults, some of the main causes of this are carcinomas, polyps, strictures, benign tumors, Meckel’s diverticulum, and colonic diverticulum. Here we present a case of intussusception which had a subserosal lipoma as a lead pathological point, but the histopathological examination revealed dual pathology for the same. A subserosal lipoma with presence of heterotopic gastric mucosa was diagnosed in the ileum as the leading pathological point of ileo-ileal intussusception. This case highlights the importance of pathological examination to know the specific cause of intestinal obstruction.